2014
DOI: 10.1002/pssa.201431289
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of Ga2O3-doped barium iron niobate ceramics

Abstract: Ga-doped BaFe 0.5 Nb 0.5 O 3 (Ba(Fe 1-x Ga x ) 0.5 Nb 0.5 O 3 ) ceramics were fabricated and their properties were investigated. All ceramics showed perovskite structure with cubic symmetry and the solubility of Ga in BFN ceramics had a limit at x ¼ 0.2. Examination of the dielectric spectra indicated that all ceramic samples presented high dielectric constants that were frequency dependent. The x ¼ 0.2 ceramic showed a very high dielectric constant (e r > 240 000 at 1 kHz) while the x ¼ 0.4 sample exhibited h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[15]. Furthermore, the result was confirmed by X-ray diffraction investigation [12]. The dielectric tenability characteristic was determined from the measurement of dielectric constant under applied electric field.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…[15]. Furthermore, the result was confirmed by X-ray diffraction investigation [12]. The dielectric tenability characteristic was determined from the measurement of dielectric constant under applied electric field.…”
Section: Resultsmentioning
confidence: 70%
“…A-site doping using La and Na as dopants, on the dielectric properties of BFN have also been studied [10,11]. Our previous work showed that the Ga doped BFN showed better dielectric properties as compared to unmodified BFN [12]. In the present work, we report a further study into the effect of type of electrode on the dielectric properties of the Ga doped BFN.…”
Section: Introductionmentioning
confidence: 76%
“…This may be due to the change in resistance at bulk grain and grain boundary of the samples after the additive was added. These resistances can be changed under the applied magnetic field [9,32], as a result in a change of r value [33].…”
Section: Resultsmentioning
confidence: 99%
“…The co-existence of Fe 2+ and Fe 3+ ions can give rise to the Fe 2+ /Fe 3+ polaron hopping conduction mechanism. Further, the Fe 2+ concentration is known to be sensitive to temperature, and have increases with increasing temperature [13]. After adding BZT an heterogeneous conduction may have occurred [13] due to BZT and SFN having a large difference of conduction which alter bulk grain and grain boundary characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the Fe 2+ concentration is known to be sensitive to temperature, and have increases with increasing temperature [13]. After adding BZT an heterogeneous conduction may have occurred [13] due to BZT and SFN having a large difference of conduction which alter bulk grain and grain boundary characteristics. This can produce the Maxwell Wagner polarization mechanism in the sample and result in the very high dielectric constants.…”
Section: Resultsmentioning
confidence: 99%